Engaging with sleep: male definitions, understandings and attitudes. - Meadows, R; Arber, S; Venn, S; Hislop, J (2008)
Recent literature has highlighted the sociological significance of sleep and has suggested that sleep offers a 'window' onto the gendered nature of our lives. Yet within this body of work men's sleep has been largely ignored. This paper seeks to rectify this omission and situates itself at the intersection between literature on the sociological aspects of sleep and social-constructionist-orientated writings on men's health. It draws upon qualitative data from 40 men to investigate male understandings of, and attitudes towards, sleep. At first glance, it could be suggested that men have little regard for sleep, and are prone to taking risks with their dormancy. Viewed in this way sleep becomes an instrument used in the negotiation of status and power and intrinsically bound up with the demonstration of masculinities. Yet, men's relationship with sleep is more complex than this. Amongst other things, the men within the present study were embroiled in a function/non-function dichotomy. Sleep was seen as needed for the praxis of 'father', 'worker', 'husband' and 'mate' but was also considered as something which should not get in the way of performing these roles.